2000
DOI: 10.1016/s0895-7061(99)00187-9
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to cadmium and conventional and ambulatory blood pressures in a prospective population study

Abstract: This prospective population study investigated in a random sample of 692 subjects (age 20-83 years) how changing environmental exposure to cadmium influenced blood pressure (BP) and the incidence of hypertension. At baseline (1985 to 1989; participation rate, 78%) and follow-up (1991 to 1995; re-examination rate, 81%), blood pressure was measured by conventional sphygmomanometry (CBP; 15 readings in total) and, at follow-up, also by 24-h ambulatory blood pressure monitoring (ABP). Systolic/diastolic CBP at bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 27 publications
2
55
0
1
Order By: Relevance
“…Because of this time lag, the correlations of the biomarkers of internal exposure with the concentrations of the toxic metals in house dust and vegetables might have been stronger than those currently reported. Indeed, we previously demonstrated that over a 5-year period, with a massive decrease in the emissions of the non-ferrous smelters in the polluted area (Staessen et al, 1995) and the gradual introduction of unleaded fuel in Belgium, the concentrations of cadmium and lead in blood dropped by approximately 30% (Staessen et al, 1996a(Staessen et al, , b, 2000, whereas the urinary excretion of cadmium declined by only 15% (Staessen et al, 2000). That the associations of the blood concentrations of cadmium and lead with the external markers of exposure were similar as those for 24-h urinary cadmium underscores the consistency of our findings and might reflect the persistent nature of these pollutants in house dust (Paustenbach et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Because of this time lag, the correlations of the biomarkers of internal exposure with the concentrations of the toxic metals in house dust and vegetables might have been stronger than those currently reported. Indeed, we previously demonstrated that over a 5-year period, with a massive decrease in the emissions of the non-ferrous smelters in the polluted area (Staessen et al, 1995) and the gradual introduction of unleaded fuel in Belgium, the concentrations of cadmium and lead in blood dropped by approximately 30% (Staessen et al, 1996a(Staessen et al, , b, 2000, whereas the urinary excretion of cadmium declined by only 15% (Staessen et al, 2000). That the associations of the blood concentrations of cadmium and lead with the external markers of exposure were similar as those for 24-h urinary cadmium underscores the consistency of our findings and might reflect the persistent nature of these pollutants in house dust (Paustenbach et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…However, the influence of Cd on the cardiovascular system remains controversial. Cross-sectional and prospective studies by Staessen et al (2000) showed that conventional or 24-h ambulatory blood pressure, or the risk of hypertension or cardiovascular diseases risk (Nawrot et al 2008) in environmentally exposed populations were not associated with 24-h urinary Cd. Subjects with Itai-Itai disease also failed to develop hypertension (Nakagawa and Nishijo 1996).…”
Section: Blood Pressure and Effects On Arteriesmentioning
confidence: 96%
“…1,2) However, other epidemiological studies in Belgium produced evidence inconsistent with the hypothesis that environmental exposure to Cd leads to an increase in blood pressure and a higher prevalence of hypertension. 3,4) Although many reports have shown an increase in blood pressure in experimental animals treated parentally with Cd, 5,6) the effects of dietary administration of Cd over long periods and at low levels on blood pressure remain unknown.…”
Section: Introductionmentioning
confidence: 99%